Crocodile story - Pootchemunka, Eva, 1933-2006.; Pootchemunka, Pat, 1938-; Yunkaporta, Koppa, 1919-1992.; Namponan, Garry, 1960- ([Thuringowa, Qld.] : Black Ink Press, 2007)
"On 3 August 1953 Samuel Pootchemunka of Aurukun, a hunter aged 60 years, was awarded The Royal Humane Society of Australasias Silver Medal for the courage and humanity he displayed in rescuing Eva aged twenty and her baby Beulah aged ten months, from the crocodile. this is an illustrated account of that event. A version of this story is published in Aurukun Oral History and held in the AIATSIS audio-visual archives."--Provided by publisher.
Keywords: Pootchemunka, Samuel; Crocodile attacks -- Queensland -- Archer River; Crocodiles -- Queensland -- Archer River; Aboriginal Australians -- Queensland -- Aurukun Region; Archer River (Qld.); Wik Mungkan people (Y57) (Qld SD54-07); Stories and motifs - Crocodiles; Aurukun Region (Qld.); Archer River (Qld NW Cape York SD54-07, SD54-08)